1995
DOI: 10.2307/1542195
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Spermatozoa of the Hagfish Eptatretus burgeri (Agnatha)1

Abstract: Live motile spermatozoa of the hagfish Eptatretus burgeri were obtained for the first time, and their fine structure was examined. The spermatozoon is characterized by an extremely long midpiece. Two of the four midpiece mitochondria are extensively elongated and extend through almost the entire length of the tail. The acrosome contains electron-dense and less dense materials in two different compartments. Amorphous subacrosomal material lies between the acrosome and the nucleus. No distinct perforatorium rod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Intact mature spermatozoon of the hagfish, E. burgeri , possesses the acrosomal complex at the apex of the elongated sperm head (Morisawa 1995). The intact acrosome was round at the apical end of the sperm head in scanning electron micrographs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intact mature spermatozoon of the hagfish, E. burgeri , possesses the acrosomal complex at the apex of the elongated sperm head (Morisawa 1995). The intact acrosome was round at the apical end of the sperm head in scanning electron micrographs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lamprey has an acrosome with a preformed axial rod in the unreacted spermatozoon (Stanley 1967; Nicander & Sjöden 1971; Jaana & Yamamoto 1981), whereas in the sturgeon, the spermatozoon has both granular and filamentous materials in the subacrosomal region (Cherr & Clark 1984). The hagfish spermatozoon has an acrosome without distinct filamentous structures or axial rod within the subacrosomal material (Jespersen 1975; Morisawa 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the duration of motility is temperature dependent and species specific, varying from w1 min for L. yokohamae and L. herzensteini, 2 min for Verasper moseri, 5 min for Pecten maximus, and 7-10 min for Vaejovis variegatus, to an hour in cod (Trippel & Morgan 1994) at 2 8C in the latter case. In hagfish, it was observed that sperm motility can last for periods up to 10 min (Morisawa 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The morphological structure is primitive and similar to those described in most teleostean fishes, which typically do not have acrosomes (Lahnsteiner and Patzner, ). For teleosts, an acrosome‐less head is compensated by presence of a narrow funnel‐shaped micropyle in the egg serving as opening pore to permit sperm passage to fertilize the egg (Morisawa, ). However, some fish species, e.g.…”
Section: Discussionmentioning
confidence: 99%